2023
DOI: 10.1088/1748-0221/18/01/p01006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of planar coded aperture imaging reconstruction methods

Abstract: Imaging distributions of radioactive sources plays a substantial role in nuclear medicine as well as in monitoring nuclear waste and its deposit. Coded Aperture Imaging (CAI) has been proposed as an alternative to parallel or pinhole collimators, but requires image reconstruction as an extra step. Multiple reconstruction methods with varying run time and computational complexity have been proposed. Yet, no quantitative comparison between the different reconstruction methods has been carried out so far. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, optimizing random masks for various applications is not trivial and often requires artificial intelligence search methods (e.g., McMillan et al (2015)). A recent study by Meiaaner et al (2023) compared additional analytical reconstruction techniques such as the Maximum Likelihood Expectation Maximization (MLEM) algorithm and Wiener filtering to standard decoding, as well as Convolutional Encoder-Decoder methods. The authors found that MLEM provides the highest reconstruction quality but at the expense of nearly a 45× increase in computation time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, optimizing random masks for various applications is not trivial and often requires artificial intelligence search methods (e.g., McMillan et al (2015)). A recent study by Meiaaner et al (2023) compared additional analytical reconstruction techniques such as the Maximum Likelihood Expectation Maximization (MLEM) algorithm and Wiener filtering to standard decoding, as well as Convolutional Encoder-Decoder methods. The authors found that MLEM provides the highest reconstruction quality but at the expense of nearly a 45× increase in computation time.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that MLEM provides the highest reconstruction quality but at the expense of nearly a 45× increase in computation time. Meiaaner et al (2023) did suggest, however, that a Convolutional Encoder-Decoder neural network could outperform all analytical decoding techniques, producing images with better contrast. Neural networks have been found optimal over analytical methods in other coded aperture studies (e.g., Zhang et al (2019)), and even for identifying sources within the PCFOV (e.g., Liu et al (2021)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collimator performance dominates current IGC capabilities; this, therefore, represents a research area with a high potential to improve overall performance. Whilst pinhole and parallel-hole collimator geometries are well-established and understood, diverging and coded-aperture designs are still in flux, with active research into both collimator design and image reconstruction [122][123][124]. This development is supported by the rapid progression of additive manufacturing for high-Z materials, although currently cost remains a barrier to this technology's uptake.…”
Section: Outlook For the Next 10 Yearsmentioning
confidence: 99%
“…Charge-sharing correction algorithms, which have already been implemented for multiple detector systems, offer the ability to recover the spectral performance lost by small-anode-pixel semiconductor detectors and allow for exceptional energy resolution and spatial resolution simultaneously [118,147,148]. The application of deep learning and neural networks to the optimisation of current dataprocessing tasks looks to advance IGCs in a range of ways, including: improved energy resolution reconstruction, sub-pixel event positioning, improved event localisation, and improved near-field coded-aperture image reconstruction [119,124,149,150].…”
Section: Outlook For the Next 10 Yearsmentioning
confidence: 99%